Book Reviews (Journal of Finance, 1992)
Book reviewed in this article: Capital Markets: Institutions and Instruments . By FRANK J. FABOZZI and FRANCO MODIGLIANI. Finance in Continuous Time: A Primer . By DAVID C. SHIMKO. Global Financial Deregulation: Commercial Banking at the Crossroads . By ITZHAK SWARY and BARRY TOPF. Quasi‐Rational Economics . By RICHARD H. THALER.